A randomized comparative study of MIP and MMR vaccine for the treatment of cutaneous warts - Amandeep Kaur; Balvinder Kaur Brar; Sumir Kumar; Sukhmani Kaur Brar; Amarbir Singh Boparai; Neerja Puri (Wolters Kluwer Medknow Publications, 2021)
Objectives: To evaluate and compare the efficacy of MMR vaccine and MIP vaccine for resolution of Cutaneous warts (Cw). Methods: The hospital-based prospective randomized interventional study was done where a total of 60 patients of Cw were divided into two groups of 30 patients each: Group A received 0.1 ml of intralesional injection of MIP vaccine and Group B received 0.5 ml of MMR vaccine. The treatment protocol involved three intralesional injection of vaccines at intervals of 3 weeks (maximum of three injections). The follow-up was done every 4 weeks for at least 24 weeks for the comparison of the two groups. The primary outcomes were the decrease in size of the wart or clearance of primary warts. The secondary outcomes were the improvement in the distant warts and any complications related to the use of vaccines. The data were entered in MS Excel and analyzed using SPSS 17.0 version. A P value of <0.05 was considered statistically significant. Results: The baseline demographic and wart characteristics were comparable between the two groups (P > 0.05). As compared to MMR, MIP showed an early (9.41 vs 11.71 weeks, P = 0.027), and a significantly higher complete response (90% vs 76.67%) with P < 0.05. The less duration of the warts was significantly associated with the higher complete response (P < 0.05) in both the groups. The common side effects were erythema/inflammation [19 (63.34%)] in Group A and pain during the injection [19 (63.34%)] in Group B with P < 0.0001. Conclusion: In conclusion, MIP intralesional injections have a quicker response and are more efficacious compared to MMR in the treatment of Cw, though each vaccine carries its own sets of side effects.